Global Existence of a Chemotactic Movement with Singular Sensitivity by Two Stimuli - Heping Ma (Discrete Dynamics in Nature and Society)
In this study, we deal with the chemotaxis system with singular sensitivity by two stimuli under homogeneous Neumann boundary conditions in a bounded domain with smooth boundary. Under appropriate regularity assumptions on the initial data, we show that the system possesses global classical solution. Our results generalize and improve previously known ones.